2018
DOI: 10.1039/c7lc00970d
|View full text |Cite
|
Sign up to set email alerts
|

Multi-size spheroid formation using microfluidic funnels

Abstract: We present a microfluidic platform for automatic multi-size spheroid formation within constant volume hanging droplets (HDs) from a single inlet loading of a constant cell concentration. The platform introduces three technological improvements over the existing spheroid formation platforms: 1) cell seeding control is achieved by enrichment of a cell solution rather than dilution; 2) cell seeding in each HD is fully independent and pre-programmable at the design stage; 3) the fabricated chip operates well using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…The possibility to use only 150 cells per spheroid can be crucial when working with rare and hard to expand cells, such as primary patient derived tumor cells. Spheroids used in research vary in their sizes from 50 to 1000 µm . Even though spheroids smaller than 200 µm usually do not develop necrotic core, it was shown that even very small spheroids, with diameter < 100 µm, have oxygen gradient and develop hypoxia and activation of hypoxia‐responsive element (HRE) already after 2 days of culturing, which confirms their physiological similarities to in vivo tumors.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The possibility to use only 150 cells per spheroid can be crucial when working with rare and hard to expand cells, such as primary patient derived tumor cells. Spheroids used in research vary in their sizes from 50 to 1000 µm . Even though spheroids smaller than 200 µm usually do not develop necrotic core, it was shown that even very small spheroids, with diameter < 100 µm, have oxygen gradient and develop hypoxia and activation of hypoxia‐responsive element (HRE) already after 2 days of culturing, which confirms their physiological similarities to in vivo tumors.…”
Section: Resultsmentioning
confidence: 77%
“…Droplet Microarray platform is flexible and allows to grow spheroids of different sizes by varying initial cell number and size of hydrophilic spots. It was shown that spheroids of different sizes might respond differently to drug treatment, therefore, suitable size of spheroids should be chosen depending on application. In this study, our goal was to demonstrate formation and screening of spheroids from low cell numbers to enable large screenings in the 3D format using physiologically relevant rare and difficult to expand cells, such as primary patient‐derived cells and stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…First, not all cell lines are able to form and be maintained as spheroids, thereby reducing the number of models. Second, 3D models confer heterogeneity in the concentrations of nutrients, oxygen and lactate within the spheroids, which are dependent on diffusion and therefore spheroid size 24,25 . Thus, consistent control of spheroid size is desired to reduce variability in experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Second, a large number of cells are needed to achieve the high seeding densities required for the uniform spheroid production regime described here. While this is not a concern for cell lines, adapting this platform for limited primary cells will require some modifications, such as a funnel structure to feed a small volume of cell suspension into a single well [30]. Although this would increase device complexity and would require a pipetting step for each spheroid, it would enable production of spheroids from precious cell material.…”
Section: Current Technical Limitationsmentioning
confidence: 99%
“…Scaled-up methods have been introduced, including forming aggregates in non-adhesive microwells [21] or in stirred vessels [1,[21][22][23], but these stochastic techniques have relatively poor control over aggregate size, which is a critically important parameter for aggregate function. More technically advanced strategies such as the use of microarrayed [3,7,[24][25][26] or microfluidic systems [27][28][29][30][31] have also been developed to provide controlled and addressable culture models, but these are challenging to adopt in standard wet labs as microfluidic systems typically require considerable expertize to fabricate and operate [32].…”
Section: Introductionmentioning
confidence: 99%